An isogeometric finite element-boundary element approach for the vibration analysis of submerged thin-walled structures. (November 2021) - del Toro Llorens, Alvaro; Kiendl, Josef
Highlights: High order NURBS-based FEM-BEM solver. Novel master–slave approach to enforce the G1 continuity for geometries with poles. Non-matching fluid–structure interface discretizations without a projection scheme. Accurate and efficient calculation of the wet eigenfrequencies of shell structures. Abstract: In this paper, the isogeometric formulations of the finite element and boundary element methods are applied to the dynamic analysis of thin-walled structures submerged in an infinite, inviscid, and incompressible fluid medium. This fluid–structure interaction problem is decoupled using the modal analysis technique, and the fluid effect on the structure is taken into account through the generalized added mass matrix. The structure is modeled with NURBS-based Kirchhoff–Love shell elements. The fluid response is computed using a regularized boundary integral equation. We take advantage of the geometry preserving property of the NURBS refinement techniques to reduce the computational cost without the need for a projection scheme. The implementation is benchmarked with three test cases, and good accuracy is obtained for a relatively low number of degrees of freedom.